11th grade students' awareness of English reading strategies: a descriptive research at Yen Vien High school= Nhận thức của học sinh lớp 11 về chiến lược học đọc – Một nghiên cứu mô tả ở trường cấp 3 Yên Viên M.A. Thesis Linguistics : 60 14 10 - Hoàng, Thị Oanh (University of Languages and International studies, 2017)
M.A. Thesis. English teaching methodology -- University of Languages and International studies. Vietnam National University, Hanoi, 2011